2014
DOI: 10.1371/journal.pone.0105698
|View full text |Cite
|
Sign up to set email alerts
|

MARCH2: Comparative Assessment of Therapeutic Effects of Acarbose and Metformin in Newly Diagnosed Type 2 Diabetes Patients

Abstract: BackgroundThe data of MARCH (Metformin and AcaRbose in Chinese as the initial Hypoglycaemic treatment) trial demonstrated that acarbose and metformin have similar efficacy as initial therapy for hemoglobin A1c (HbA1c) reduction in Chinese patients with newly diagnosed type 2 diabetes. We investigated whether the therapeutic efficacy was diversified under different body mass index (BMI) status.MethodsAll 784 subjects were divided into normal-weight group (BMI<24 kg/m2), overweight group (BMI 24–28 kg/m2) and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Interestingly, because the patients were on different doses of metformin treatment, we re-analyzed the data according to the dose regime. Since the maximal metformin dose was 2500 mg/day, we considered a cut-off of 1500 mg/day for the low and high doses; 1500 mg/day is the standard dose required in pharmacological studies evaluating a second drug in T2DM patients already treated with metformin [25]. Although the mean value of the nucleosome levels in the high metformin dose group of T2DM patients was lower than that of the low dose group, they were not statistically different (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, because the patients were on different doses of metformin treatment, we re-analyzed the data according to the dose regime. Since the maximal metformin dose was 2500 mg/day, we considered a cut-off of 1500 mg/day for the low and high doses; 1500 mg/day is the standard dose required in pharmacological studies evaluating a second drug in T2DM patients already treated with metformin [25]. Although the mean value of the nucleosome levels in the high metformin dose group of T2DM patients was lower than that of the low dose group, they were not statistically different (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…In metformin or AGI treated patients, the results from a prospective, multicenter, open-label study in newly diagnosed Chinese type 2 diabetes [7], indicated that baseline BMI had no impact on glycemic control, weight change or other efficacy measures. Another post-hoc analysis [14] of a randomized controlled trial also concluded that both acarbose and metformin similarly decreased the HbA1c levels regardless of the BMI status. In DPP-4 inhibitors treated patients, Schweizer reported a pooled-analysis [15] and the results indicated that it was efficaciously independent of the BMI group.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design, investigative centers, and patient inclusion/exclusion criteria for the MARCH study have been reported previously 11,12 . The patients had either not taken antidiabetic medication previously or had received only short-term (1 month) treatment that had been discontinued for 3 months prior to enrollment in the study.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The effects of both drugs in reducing HbA1c were similar regardless of the patients' body mass index (BMI) 12 . Because certain populations may respond more favorably to either acarbose 13 or metformin, the present post-hoc analysis was undertaken to identify the characteristics of participants in the MARCH trial at baseline and in the treatment period that may be associated with greater efficacy in achieving a HbA1c level <7% (<53 mmol/mol).…”
Section: Introductionmentioning
confidence: 99%